(untitled) (Journal of Tourism & Adventure, 2019)
Ecotourism is a growing arena of tourism industry and is a potential tool for sustainable development. This study focuses identifying potentials of ecotourism in Tinjure-Milke-Jaljale (TMJ) area in Eastern Nepal via assessing flow of tourists, purpose for visits, major natural attractions, physical infrastructures and human resources available in the region. Direct interviews were conducted with respondents purposively selected from 50 households using structured questionnaires. Demographic variables and visit purpose were expressed in numbers and percentage using MS-Excel soft ware. A descriptive analysis was performed for the natural features, human resource, physical infrastructures and cultural entities which were collected using standard checklist. Results showed that TMJ was visited by approximately 1, 00,000 internal and 600 international tourists throughout the year in 2018.Th e main purpose of visit to TMJ was to adhere the beauty of rhododendron or landscape followed by religious, study and recreational purposes respectively. While 80% percent of the respondents were aware of the need towards biodiversity conservation focusing Rhododendron forests which listed as a major attraction in the region and 78% agreed to impacts of tourism the area, 75% were unfamiliar with the concept ecotourism. The region with more than 80% forest coverage harbors natural and cultural attractions such as Deurali Bhulke picnic spot, Rock and Rhododendron Garden, Basantapur Botanical garden and view Tower, Tinjure Dada Pathivara Temple, Gupha Pokhari, Singhabahini Devi Temple, Gaunkhuridham, Siddhakali, Sabhapokhari. The present natural and culturally important areas in TMJ show good prospects for ecotourism. However, a detailed study focusing number of seasonal flow of tourists and services provided addressing visitor’s perception is seen important to improve ecotourism.